The Love Booth and Six Companion Plays - Goldstein, Tara; Salisbury, Jenny; hicks, benjamin lee; Owis, Bishop; Reid, Kael (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2025)
This article describes and reports on findings from a project called The Love Booth and Six Companion Plays (2021–2023). The overall goal of the project was to conduct archival research on moments of activism and care that have challenged cis-heteronormativity and racism and then share these moments through verbatim theatre scripts and performances. Working with an ethic of community care, and a lens that examines the intersections of cis-heteronormativity with other forms of structural discrimination (such as anti-Asian racism, anti-Black racism, anti-Indigenous racism, and settler colonialism), the project asked and answered the following research question: What kinds of activism and care in the 1970s and 1980s challenged cis-heteronormativity and racism in North America?